Impact of relationship marketing on customers loyalty of Islamic banks in the state of Kuwait - Faraj Aldaihani, Faraj Mazyed; Ali, Noor Azman (International Journal of Scientific & Technology Research, 2019)
This study aimed to investigate the impact of relationship marketing on Customers Loyalty of Islamic banks in the state of Kuwait. Five dimensions of relationship Marketing was included in the study: Trust, Communication, Commitment, Competence, and Cooperation. On the other hand, customer loyalty was measured by two dimensions: Attitudinal Loyalty and Behavioral Loyalty. To achieve the aim of this study, a random simple sampling was applied as a sampling technique. Population of this study was the customers of four Islamic banks in the state of Kuwait, they were provided with 600 questionnaires, (560) responses were valid for test. The researchers used the descriptive and analytical methods. The results indicated that there is a significant statistical impact of relationship marketing dimensions (Trust, Communication, Commitment, Competence, and Cooperation) on Customers Loyalty of Islamic banks in the state of Kuwait. Based on the study results, the researchers recommend managers and decision makers of Islamic banks in Kuwait to be committed to their customers in terms of the needs and desires, and to provide timely services to customer to win their commitment in return.